Effect of trauma distress, trauma dissociative experience and life satisfaction among earthquake victims in Sabah, Malaysia - Ferlis Bullare @ Bahari; Allya Cassandra Alim; Mohd Dahlan A. Malek; Lailawati Madlan; Jasmine Adela Mutang; Wan Anor Wan Sulaiman (Medwell Journals, 2017)
For years, many researchers have been working on ways of examining the psychological effect of earthquakes among victims who have experienced trauma. The goal of this study is to examine the relationship between trauma distress, associative trauma and life satisfaction among earthquake victims in Ranau, Sabah. A survey was conducted in a sample of 136 students from the Ranau area, 1 month after the earthquake. Demographics were obtained from participants using a self-administered questionnaire, fear and sense of helplessness were assessed with the Peritraumatic Distress Inventory (PDI), peritraumatic dissociative experiences were assessed with the Peritraumatic Dissociative Experiences Questionnaire (PDEQ) and life satisfaction was assessed with the cantrill’s vertical visual-analogue scale ladder of life satisfaction. The results showed that was a significant negative effect of traumatic distress towards life satisfaction whereas dissociative traumatic experience did not have significant effect on life satisfaction. In addition, there was a significant and positive relationship between trauma distress and dissociative trauma among earthquake victims in Ranau. The findings suggest that concern over earthquake disaster was strongly associated with psychological distress. Reliable, accurate information on earthquake disaster might reduce psychological effects among victims.